City delineation in European applications of LUTI models: review and tests. Issue 1 (2nd January 2018) - Thomas, Isabelle; Jones, Jonathan; Caruso, Geoffrey; Gerber, Philippe
ABSTRACT: This paper stresses the lack of attention paid to the geographical definitions of cities in LUTI models as one key detrimental aspect to transferring and generalising LUTI results. First, the argumentation develops from a meta-analysis of peer-reviewed publications about LUTI applications in European cities. We show that most authors do not assess findings against potential geographical biases. Second, theoretical simulations are conducted with UrbanSim applied to a synthetic urban area. By varying the geographical limits of the system and population endowments, our simulations confirm that the absence of control on city delineation weakens the results. Finally, the paper suggests methodological guidelines to improve the comparability of LUTI applications and push forward their theoretical agenda.